Vous êtes sur la page 1sur 42

max z = 3x 1 + 5x 2

x

3x

x

1

1

1

+

2x

2x

x

2

2

2

4

(1)

12

(2)

18

(3)

0

(4)

0

(5)

1 1 1 + 2 x 2 x x 2 2 2 ≤ 4 (1) ≤

 

 

 

 

 

 

 

 

 

 

x 1

x 2

max z = 3x 1 + 5x 2 .

x 1 , x 2 0.

x 1 4.

2x 2 12

3x 1 + 2x 2 18.

max z = 3x 1 + 5x 2

3x 1

+

x 1

2x

2x

x

x

2

2

1

2

4

12

18

0

0

(x 1 , x 2 )

3x 1 + 2x 2 18

3x 1 + 2x 2 = 18

3x 1

+

x

2x

2x

x

x

1

2

2

1

2

4

(1)

12

(2)

18

(3)

0

(4)

0

(5)

R n n R n a k 1 x 1 + a k 2 x

R n

n

R n

a k 1 x 1 + a k 2 x 2 +

+

a k n x n b k

R n

a k1 x1 + a k2 x 2 +

+

a kn x n = b k .

R n x R n

a k1 x 1 + a k2 x 2 +

+ a kn x n b k ,

k = 1,

, p.

R 3

x 1 + x 2 + x 3

x 1 ,

x 2 ,

x

3

1

0

OABC O

OABC O R 3 z = 3 x 1 + 5 x 2 . z =

R 3

z = 3x 1 + 5x 2 .

z = k.

3x 1 + 5x 2 = k.

z = 10, 20 36.

z = 10 , 20 36 . x ∗ = (2 , 6) .

x = (2, 6).

z = 3x 1 + 2x 2 (2, 6) (4, 3)

x x z x y x = y

R n

a k1 x 1 + a k2 x 2 +

+ a kn x n = b k ,

k I ⊂ {1,

, p}.

R n n 1 0.

OABC ABC

x 1 + x 2 + x 3 = 1

AB

x 1 + x 2 + x 3 = 1 x 3 = 0

C n = 3 0

n

n = 2 m

m = 3 c j

j b i i a ij

i j

 

 

 

.

.

.

n

a

11

a

12

.

.

.

a

1n

b

1

a

21

a

22

.

.

a

2n

b

2

 

.

a m1

a m2

a mn

b

m

c 1

c 2

.

.

.

c n

 

max z = c 1 x 1 + c 2 x 2 +

+ c n x n ,

a 11 x 1

a 21 x 1

a m1 x 1

+ a 12 x 2

+ a 22 x 2

+ a m2 x 2

+

+

+

a 1n x n

a 2n x n

a mn x n

x

x

x

1

2

n

b 1 ,

b 2 ,

b m ,

0,

0,

0.

n m + n n

  A (m × n),

c (n × 1),

max z = c T x,

Ax

x

b (m × 1)

x (n × 1)

.

b,

0.

x

S

S = {x R n | Ax b,

x 0}.

x S

x S,

c T x c T x,

max z = 4x 1 + 3x 2

3x

7x

1

1

+

+

4x

2x

2

2

x 1 , x 2

12

14

0

max z = 5x 1 + 4x 2

x

2x

3x

1

1

1

+

+

+

x

x

x

2

2

2

x 1 , x 2

20

35

12

0

max z = 3x 1 + 5x 2

x 1

3x 1

x 1

+

2x

2x

2

2

x 2

4

12

18

0

0

(0 , 0) (0 , 6) (0 , 6) (2 , 6) (0 ,

(0, 0) (0, 6) (0, 6) (2, 6) (0, 6) (4, 3)

  A (m × n),

c (n × 1),

max z = c T x,

Ax

b,

x 0

b (m × 1)

x (n × 1).

n m+n

m

n

3x 1 + 2x 2 18.

3x 1 + 2x 2 + x 3 = 18,

x 3

x 3 0.

2x 1 + x 2 4,

x 3 0.

2x 1 + x 2 x 3 = 4,

max z = 3x 1 + 5x 2

x

3x

1

1

x 1 ,

2x

+2x

2

2

x 2 ,

+x 3

x 3 ,

+x4

x 4 ,

=

=

=

x 5

+x

5

4

12

18

0

(3, 2)

(3, 2, 1, 8, 5)

R 5

m = 3

n + m = 2 + 3 = 5 n = 2

x

1

3x 1

2x 2

+2x 2

+x 3

=

4

 

+x4

=

12

 

+x 5

=

18

x 1 x 2

n R n+m m

x 3 , x 4 x 5

x 3 = 4

x 4 = 12

x 5 = 18.

n m

 

x 1 = 0,

x 2 = 0

x 3 = 4,

x 4 = 12,

x 5 = 18

(0, 0),

(0, 6), (2, 6), (4, 3), (4, 0)

(0, 9), (4, 6) (6, 0)

(x 1 , x 2 )

(x 3 , x 4 , x 5 )

x 1 , x 2

(0, 0)

(4, 12, 18)

x 1 , x 4

(0, 6)

(4, 0, 6)

x 1 , x 5

(0, 9)

(4, 6, 0)

x 4 , x 5

(2, 6)

(2, 0, 0)

x 3 , x 4

(4, 6)

(0, 0, 6)

x 3 , x 5

(4, 3)

(0, 6, 0)

x 2 , x 3

(4, 0)

(0, 6, 6)

x 2 , x 5

(6, 0)

(2, 12, 0)

x

x

x

x

x

1

2

3

4

5

=

=

=

=

=

0,

0,

4,

12,

18,

x

x

x

x

x

1

2

3

4

5

= 0,

= 6,

= 4,

= 0,

= 6

x

x

1

2

= 0,

= 0,

x

x

1

2

= 2,

= 6

b i 0, i = 1,

n,

(x 1 , x 2 ) = (0, 0).

x

3x

1

1

2x

+2x

2

2

+x 3

=

4

 

+x4

=

12

 

+x 5

=

18,

x 3 = 4

x 4 = 12

x 5 = 18.

(0, 0, 4, 12, 18).

z = 3x 1 + 5x 2 = 3 × 0 + 5 × 0 = 0,

z = 3x 1 + 5x 2 .

x 1 z 3

x 2 z 5

z

(ox 2 ) (0, 6)

x 4 x 2

x 1

x 2

x

x

x

3

4

5

= 4

=

0

12 2x 2

0

= 18 2x 2

0

x 2 12

2

=

6

x 2 18

=

9.

2

x 4

x 2 = 6

z

3x

x

3x

1

1

1

5x

2x

+2x

2

2

2

 

=

0

(0)

+x 3

=

4

(1)

 

+x 4

=

12

(2)

 

+x 5

=

18.

(3)

x 2 x 4 x 2

x 4

1 x 2

1/2

(2 ) = (2) × 1

2

x 2

(3 ) = (3) (2)

(0 ) = (0) + 5 × (2 ).

z

3x 1

x 1

3x 1

x

2

+x 3

+

5

2

x 4

=

=

=

x 4 +x 5 =

+ 1 2 x 4

30

(0 )